The Role of Primary School Teachers in Encouraging Students’ Musical Creativity through the Planning of School Events - Strah, Alja (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter highlights the key role of primary school teachers in fostering students’ musical creativity through the planning and execution of school events. Musical creativity is presented as a vital component of the educational process, contributing to students’ holistic development, including the enhancement of cognitive, emotional, and social skills. The role of teachers is emphasized, as their example and approach create an encouraging environment for students to express themselves and nurture their creativity. The importance of planning musical activities that actively involve students in all stages of preparation and performance of school events, while fostering peer cooperation, is underscored. Teacher self-reflection and continuous professional development are crucial, as their expertise and commitment enrich the cultural life of the school and the wider community.